Cash Flow News and Stock Price Dynamics - PETTENUZZO, DAVIDE; SABBATUCCI, RICCARDO; TIMMERMANN, ALLAN (Journal of Finance, 2020)
ABSTRACT We develop a new approach to modeling dynamics in cash flows extracted from daily firm‐level dividend announcements. We decompose daily cash flow news into a persistent component, jumps, and temporary shocks. Empirically, we find that the persistent cash flow component is a highly significant predictor of future growth in dividends and consumption. Using a log‐linearized present value model, we show that news about the persistent dividend growth component predicts stock returns consistent with asset pricing constraints implied by this model. News about the daily dividend growth process also helps explain concurrent return volatility and the probability of jumps in stock returns.